Sequential vs concurrent epirubicin and docetaxel as adjuvant chemotherapy for high-risk, node-negative, early breast cancer: an interim analysis of a randomised phase III study from the Hellenic Oncology Research Group - Mavroudis, Dimitrios (Br J Cancer, 2017)
BACKGROUND: Sequential anthracyclines and taxanes are standard adjuvant chemotherapy for patients with high-risk axillary node-positive breast cancer. We compared a sequential to a concurrent regimen in high-risk node-negative early breast cancer. METHODS: Patients were eligible if they had tumours >2 cm or T1c with two of the following characteristics: no oestrogen receptor (ER) and progesterone receptor (PR) expression, histological grade III, Ki67 >40% and vascular, lymphovascular or perineural invasion. They were randomised to receive four cycles of epirubicin 90 mg m(−2) followed by four cycles of docetaxel 75 mg m(−2) (sequential regimen) or six cycles of epirubicin 75 mg m(−2) plus docetaxel 75 mg m(−2) (concurrent regimen). All chemotherapy cycles were administered every 21 days with G-CSF prophylaxis only for the concurrent arm. The primary endpoint was disease-free survival (DFS). RESULTS: Between 2001 and 2013, 658 women received the sequential (n=329) or the concurrent (n=329) regimen. The median age was 53 years, 43.9% of the patients were premenopausal and of the tumours 44.2% were ⩽2 cm, 52.7% histological grade 3 and 35.3% hormone receptor-negative. After a median follow-up of 70.5 months, there were 29 (8.8%) vs 42 (12.8%) disease relapses (P=0.102) and 11 (3.3%) vs 19 (5.8%) deaths (P=0.135), in the sequential and concurrent arm, respectively. The 5-year DFS rates were 92.6% vs 88.2% for sequential and concurrent arm, respectively (hazard ratio (HR): 1.591; 95% confidence interval (CI): 0.990–2.556; P=0.055). Toxicity included grade 2–4 neutropenia in 54% vs 41% (P=0.001), febrile neutropenia 2.7% vs 6.1% (P=0.06), nausea/vomiting 18.5% vs 12.4% (P=0.03) of patients in the sequential and concurrent arm. There were no toxic deaths. CONCLUSIONS: Sequential compared with the concurrent administration of anthracyclines and taxanes is associated with a non-significant but possibly clinically meaningful improvement in DFS. In the era of molecular selection of patients for adjuvant chemotherapy, this study offers valuable information for the optimal administration of anthracyclines and taxanes in patients with node-negative disease.